In Situ Optical Studies on Morphology Formation in Organic Photovoltaic Blends. Issue 10 (13th September 2021) - Liu, Yanfeng; Yangui, Aymen; Zhang, Rui; Kiligaridis, Alexander; Moons, Ellen; Gao, Feng; Inganäs, Olle; Scheblykin, Ivan G.; Zhang, Fengling
Abstract: The efficiency of bulk heterojunction (BHJ) based organic solar cells is highly dependent on the morphology of the blend film, which is a result of a fine interplay between donor, acceptor, and solvent during the film drying. In this work, a versatile set‐up of in situ spectroscopies is used to follow the morphology evolution during blade coating of three iconic BHJ systems, including polymer:fullerene, polymer:nonfullerene small molecule, and polymer:polymer. the drying and photoluminescence quenching dynamics are systematically study during the film formation of both pristine and BHJ films, which indicate that the component with higher molecular weight dominates the blend film formation and the final morphology. Furthermore, Time‐resolved photoluminescence, which is employed for the first time as an in situ method for such drying studies, allows to quantitatively determine the extent of dynamic and static quenching, as well as the relative change of quantum yield during film formation. This work contributes to a fundamental understanding of microstructure formation during the processing of different blend films. The presented setup is considered to be an important tool for the future development of blend inks for solution‐cast organic or hybrid electronics. Abstract : The reason for morphological differences in polymer:fullerene, polymer:nonfullerene small molecule, and polymer:polymer solar cells is revealed by studying their film formation through multiple in situ spectroscopies. The aggregation behavior of the higher molecular weight component, as well as the level of donor–acceptor interaction in the liquid film shows strong influence on the blend drying and its final morphology.